Prostaglandin E receptor subtype 4 regulates lipid droplet size and mitochondrial activity in murine subcutaneous white adipose tissue. Issue 9 (19th September 2017) - Ying, Fan; Cai, Yin; Cai, Yu; Wang, Yu; Ching Tang, Eva Hoi
ABSTRACT: The purpose of this study was to investigate whether genetic ablation of prostaglandin E receptor subtype 4 (EP4) affects white adipose tissue (WAT) remodeling mediated by β3 ‐adrenergic stimulation. The selective β3 ‐adrenergic agonist, CL316243 (1 mg/kg/d, i.p.) caused a greater increase in metabolic rate in EP4‐knockout mice. CL316243 fragmented the unilocular lipid droplet into multilocular lipid vacuoles and increased mitochondrial biogenesis and its activity. These changes were amplified in mice with EP4 deficiency and were selectively seen in subcutaneous WAT. The expression of fat‐specific protein (FSP)‐27, a protein that promotes fusion of triglycerides and formation of unilocular lipid droplets were diminished, whereas the expression of phosphorylated AMPK, the upstream regulator of FSP27, was enhanced in EP4‐deficient mice. The present study showed that EP4 acts as a negative regulator of WAT remodeling, it tightly coordinates rates of triglyceride storage in lipid droplets and mitochondrial respiratory function in subcutaneous white adipocytes through the phosphorylated AMPK‐FSP27 signaling axis. Thus, deletion of EP4 increases mitochondrial biogenesis and oxidative capacity in WAT, and fat mass loss ensues in mice.—Ying, F., Cai, Y., Cai, Y., Wang, Y., Tang, E. H. C. Prostaglandin E receptor subtype 4 regulates lipid droplet size and mitochondrial activity in murine subcutaneous white adipose tissue. FASEB J. 31, 4023–4036 (2017). www.fasebj.org —Ying, Fan, Cai, Yin, Cai, Yu, Wang, Yu, Ching Tang, Eva Hoi Prostaglandin E receptor subtype 4 regulates lipid droplet size and mitochondrial activity in murine subcutaneous white adipose tissue. FASEB J. 31, 4023–4036 (2017)